(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article explores the essence of economic security as a systemic property of a national economy. It substantiates its significance in ensuring sustainable development, social stability, and institutional viability. Theoretical approaches, structure, and levels of economic security are examined, as well as mechanisms of resilience under conditions of external transformation. A conceptual model is proposed, based on a systemic approach integrating digital and institutional components. This work may serve as a theoretical foundation for shaping strategic decisions in the field of economic policy.